Divergent life histories and other ecological adaptations: Examples of social-class differences in attention, cognition, and attunement to others. (29th November 2017) - Grossmann, Igor; Varnum, Michael E. W.
Abstract: Many behavioral and psychological effects of socioeconomic status (SES), beyond those presented by Pepper & Nettle cannot be adequately explained by life-history theory. We review such effects and reflect on the corresponding ecological affordances and constraints of low- versus high-SES environments, suggesting that several ecology-specific adaptations, apart from life-history strategies, are responsible for the behavioral and psychological effects of SES.